Clinical Analysis of Emergency Peripartum Hysterectomy (EPH) - Shazia Rasul, Shabnam Tahir,Lubna Riaz, Asma Gul (Journal of Rawalpindi Medical College, 2016)
Background: To find out the incidence, risk factors, indications and outcome of emergency peripartum hysterectomy, including maternal morbidity (ICU admission, blood transfusion, urological injuries, DIC) and maternal mortality. Methods: In this cross sectional study patients requiring emergency peripartum hysterectomy were included. The demographic data, risk factors , indications and outcome including maternal morbidity (ICU admission, blood transfusion, urological injuries, DIC) and maternal mortality, were recorded. Patients who required emergency peripartum hysterectomy at delivery or during 24 hours after delivery and had gestational age more than 28 weeks were included in the study. However patients who had EPH after 24 hours of delivery or before 28 weeks of gestation either due induced septic abortion or uterine perforation were excluded. Result: The total number of patients delivered during the study period was 10,030, out of which 22 patients required EPH ( 2.1 per 1000 .Most common cause of EPH was previous caesarean section and placenta previa type IV with morbidly adherent placenta (n=13 ,59.09% ).Uterine atony not responding to conservative management for EPH was second commonest reason for EPH(n=8 ,36.36%)and uterine rupture was third indication for EPH(n=1,4.55%). Fifty nine percent required admission in intensive care unit,three patients had Urological injuries and two maternal deaths occurred out of 22 patients due to disseminated intravascular coagulation. Conclusion: Emergency peripartum hysterectomy is associated with significant morbidity and maternal mortality. Abnormal adherent placenta is the most common cause of EPH. All of patients who required EPH, had previous cesarean section, so all measures should be adopted to reduce the primary cesarean section rate.